Cashew: Shell up and ship out - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
The African cashew nut is at a turning point. New European sanitary standards coupled with high transport costs are encouraging a move towards home-grown shelling operations and helping to build an increasingly solid sector...